A class of large solution of 2D tropical climate model without thermal diffusion. (8th June 2020) - Li, Jinlu; Yu, Yanghai
Abstract : In this paper, we consider the Cauchy problem of 2D tropical climate model without thermal diffusion and construct global smooth solutions by choosing a class of special initial data whose L ∞ norm can be arbitrarily large.